Antihypertensive and anti‐inflammatory actions of combined azilsartan and chlorthalidone in Dahl salt‐sensitive rats on a high‐fat, high‐salt diet. (August 2014) - Jin, Chunhua; O'Boyle, Sean; Kleven, Daniel T.; Pollock, Jennifer S.; Pollock, David M.; White, John J.
Summary Metabolic syndrome (MetS) and chronic kidney disease are global health issues. Metabolic syndrome induces hypertension and commonly results in renal damage. The optimal therapy for hypertension in MetS is unknown. Thiazide diuretics are first‐line therapy; however, these drugs may have untoward effects. In the present study we investigated the effects of azilsartan (AZL), chlorthalidone (CLTD) and their combination on blood pressure and renal injury in a rodent model with features of MetS. Dahl salt‐sensitive rats were fed high‐fat (36% fat), high‐salt (4% NaCl) diet. Groups were then treated with vehicle, AZL (3 mg/kg per day), CLTD (5 mg/kg per day) or AZL + CLTD. Mean arterial pressure was recorded continuously by telemetry. After 26 days, rats were killed humanely and their kidneys were harvested for histology. Both AZL and CLTD attenuated the rise in blood pressure compared with vehicle and the combination further reduced blood pressure compared with CLTD alone. All treatments reduced proteinuria and albuminuria. Nephrinuria was prevented only in groups treated with AZL. Nephrinuria was 57% lower and proteinuria was 47% lower with combination therapy compared with AZL alone. All treatments reduced the number of inflammatory cells in the kidney. In conclusion, in our model, AZL and CLTD lower blood pressure and exhibit renal protective effects. Treatment with AZL offers additional protection, as evidenced by lower nephrinuria and plasma monocyte chemoattractant protein‐1 levels. Combination therapy afforded the greatest protective effects and may be the best choice for hypertensive therapy in MetS.